Self-regulation and conflict goals management capabilities of ecosystem entrepreneurs: a case study of Haier ecosystem - Qin, Wenting; Zhang, Song; Lu, Baozhou (Frontiers in Psychology, 2024)
The inherent dual roles of "follower" and "leader" among ecosystem entrepreneurs inevitably introduce challenges in managing conflicting dependent and independent goals. Ecosystem entrepreneurs' capabilities in conflict goals management directly influence new venture survival and development. This single-case qualitative study explores how ecosystem entrepreneurs develop conflict goals management capabilities through self-regulation，which is not only a unique practical challenge in ecosystem entrepreneurship, but also a cutting-edge topic in current theoretical research.Through research of entrepreneurs in Haier Entrepreneurship Ecosystem, the paper finds: (1) strategic corresponding and mechanism adapting emerge as the two trigger factors enabling ecosystem entrepreneurs to recognize the equilibrium or disequilibrium between conflicting goals; (2) by leveraging self-control, grit, and metacognition, ecosystem entrepreneurs construct decoupling mechanisms for antagonistic goal recognition and coupling mechanisms for synergistic goal recognition; (3) ecosystem entrepreneurs enhance their conflict goals management capabilities by developing both segregative and synergistic management capabilities.Furthermore, this research explores the self-regulation process underlying ecosystem entrepreneurs' conflict goals management behaviors, including environmental interaction perception, conflict goals analysis, and delineation of goal relationships. Findings provide insights for ecosystem entrepreneurs on improving their conflict goals management capabilities through self-assessment and skill development.